Preparation method of TA1 and TA2 coiled tapes
By forming a dense oxide film and gradient heat-rolling at less than 800°C during the hot rolling process of titanium alloy, the serious problem of oxidation of the surface of titanium alloy is solved, the product quality and material yield of the titanium coil are improved, and economic benefits are achieved. promote.
Patent Information
- Application Number
- CN202411410458.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-10
AI Technical Summary
During the hot rolling process, titanium alloys have severe surface oxidation, resulting in many surface defects and poor tissue uniformity, which limits its large-scale application.
By forming a dense oxide film below 800°C, surface rolling is performed using gradient heating, surface deformation layer is prepared, and energy is accumulated through low-cost pre-deformation, so that subsequent heating is used to form surface recrystallization tissue, and the antioxidant ability is improved. The thickness of the oxygen permeable layer is controlled to be less than 80μm, and the ability of the coordinated deformation of the surface hard surface oxide layer and the substrate during rolling is improved.
The product quality of the titanium coil is significantly improved, the cost is reduced, and the yield is improved. A wide-format hot-rolled titanium coil with a width of 1700-2200mm, a thickness of 3-10mm and a good surface quality is prepared, which has good economic benefits.
Smart Images

Figure CN119175279A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloys, and relates to a production method for hot-rolling and continuous rolling of TA1 and TA2 slabs by EB furnace smelting, and specifically to a method for preparing TA1 and TA2 coils. Background Art
[0002] Titanium alloy has excellent properties such as low density, high specific strength and good corrosion resistance. As an important structural material, it has been widely used in aviation, aerospace, chemical industry, ships, automobiles, weapons, sports, medical and other fields. However, the large-scale application of titanium and its alloys is limited by its many surface defects, small single coil width, small coil weight, high smelting and processing costs.
[0003] Titanium alloy coils produced by hot rolling of titanium steel can improve the utilization rate of rolling lines and increase corporate profits. During the heating process of the titanium alloy slab in the heating furnace, the flame of the mixed atmosphere of blast furnace or converter gas and natural gas with low fuel value and low cost is used for heating. However, the thermal conductivity of titanium is poor, which leads to long heating time, severe surface oxidation and violent surface reaction of the titanium slab in the heating furnace of the steel enterprise. The thick surface oxygen-rich brittle layer cracks severely during the subsequent rolling process. When pure titanium is heated in the temperature range of 300℃ to 1100℃, it will experience different degrees of surface oxidation; in this temperature range, as the temperature increases, the degree of oxidation of pure titanium gradually increases. At lower temperatures of 300℃ to 500℃, the weight gain of pure titanium samples is about 0.32% to 0.34%. When the temperature is below 500℃, the performance of pure titanium is relatively stable, and the oxygen element continuously penetrates into the titanium lattice and reacts with the titanium matrix, generating a large amount of TiO2 oxide on the surface of the titanium material. When the temperature rises to 700℃ to 900℃, the oxidation weight gain increases significantly. As the temperature continues to rise, the penetration rate of oxygen elements accelerates. Matching the heating during rolling, the depth of the oxygen permeation layer can reach more than 200μm, causing the surface of pure titanium to be exposed again, thus forming a cyclic layered peeling phenomenon.
[0004] The hot rolling temperature of titanium and titanium alloys is generally lower than the α→β transformation temperature. For example, the rolling temperature of TA1 is 870℃~910℃. During the medium and low temperature heating process of titanium, as the temperature rises, the film structure is composed of titanium oxides of different densities. The oxide film increases in weight, but it is a dense layer with protective properties. When the temperature exceeds 800℃, the oxide film will gradually penetrate into the matrix, the oxide film will break, and it will no longer be dense. In the hot rolling process, in order to ensure the plasticity of the titanium billet, descaling water is basically not used, which will inevitably cause the surface hard oxide scale to be pressed into the matrix, causing surface defects and affecting the surface quality of the titanium coil. When TA1 and TA2 titanium billets are heated to rolling temperatures of 870℃~910℃, the surface oxidation products are mainly TiO2 with different densities. In addition, the titanium slabs smelted in EB furnaces have relatively coarse grains, reaching the millimeter level in size. At the same time, without VAR ingot forging, the density of the slabs is relatively small. Relatively speaking, their oxidation resistance is also different from that of the slabs forged by VAR. The stress generated by the different thermal expansion coefficients of the oxidation products generated on the surface and the matrix can easily lead to the shedding of the oxide film and the formation of microcracks in the subsequent rolling process, resulting in poor surface quality of the hot-rolled coils and severe edge cracks. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the present invention uses the slab to form a dense oxide film on the surface at a temperature below 800°C, and uses gradient heating to roll the surface to prepare a surface deformation layer. Through low-cost pre-deformation, a certain amount of deformation storage energy is accumulated after surface rolling, so that subsequent heating forms a surface recrystallization structure, and the surface fine grain area is used to improve the antioxidant ability and reduce the depth of the hard α layer; compared with conventional titanium billets, the thickness of the oxygen permeation layer is controlled to be less than 80μm after heating in a heating furnace, and the coordinated deformation ability of the surface hard surface oxide layer and the matrix during rolling is improved, thereby improving the surface quality. In order to realize this method, a series of key parameters such as titanium billet pre-deformation mode, heating system, rolling deformation amount, etc. are proposed, and finally a wide hot-rolled titanium coil with a width of 1700-2200mm, a thickness of 3-10mm, and good surface quality is prepared, which greatly improves product quality, reduces costs, and increases the yield rate, with good economic benefits.
[0006] In order to achieve the above-mentioned purpose of the invention, the present invention provides a method for preparing TA1 and TA2 coils, the process flow of which includes: ingot melting - slab preparation - slab pre-deformation - slab rolling - curling - annealing - performance testing; the preparation method includes the following steps:
[0007] S1 Ingot Melting
[0008] Sponge titanium, vanadium aluminum alloy and the like are used as raw materials and smelted into TA1 and TA2 titanium alloy ingots through a vacuum electron beam cooling hearth furnace (EB furnace). The alloy element range of the ingots conforms to the titanium and titanium alloy grade and chemical composition standard GB / T 3620.1-2016. The ingots are smelted into (240-330 mm) thick × (1500-2000 mm) wide × L mm ingots, which are ground and used as slabs to be rolled.
[0009] S2 Slab Grinding
[0010] The slab is ground and milled with a thickness of 10 to 20 mm on six sides, with four long sides chamfered by 40 to 60 mm in length and four wide sides chamfered by 50 to 80 mm in width. There are many impurities on the surface, which cannot be removed if the milling amount is too small, and excessive milling will cause metal loss and affect the yield rate. Therefore, the preferred milling thickness is 10 to 20 mm.
[0011] In the length direction, the four long sides are chamfered by 40 to 60 mm. If the chamfer is too large, the yield rate will be affected. If the chamfer is too small, the temperature will drop too quickly during rolling, which will easily cause corner cracks and affect the edge quality.
[0012] In the width direction, the four wide sides are chamfered by 50 to 80 mm. Too large a chamfer will affect the yield rate, while too small a chamfer will make it difficult for the rolled piece to bite.
[0013] S3 slab pre-deformation
[0014] ① The surface of the slab to be rolled is ground to remove the oxide layer until the bright metal is exposed, and the surface roughness Ra is less than 3.2μm. After grinding, it is loaded into the furnace and quickly moved to the 700℃~800℃ temperature zone by the walking beam for 30~60min of heat preservation before being pre-deformed. The temperature of TA1 and TA2 slabs melted in the EB furnace is high, the cooling is slow, and the original grains are relatively coarse. Rapid heating will not change its organizational structure, and there will be no mixed crystal scene.
[0015] ② The slab heating needs to ensure that the temperature difference between the upper and lower surfaces is less than 10°C. To ensure that the upper and lower surfaces are heated evenly, the slab is rotated 90° after loading into the furnace, that is, the contact position of the walking beam is in the thickness direction.
[0016] ③ Keep warm for 30 to 60 minutes, then rotate 90 degrees and roll the material out of the furnace.
[0017] ④ After the feeding is centered, the pre-deformation rolling is carried out through a four-roll mill. The length of the working roll body is greater than 2000mm, the diameter of the working roll is 350-600mm, the angular velocity of the working roll during rolling is 0.8-6rad / s, the deformation amount of a single pass is 5-30mm, and 4-6 pre-deformations are carried out. The roller diameter has high rigidity and uniform hardness distribution, which can reduce surface defects such as cracks and peeling during rolling, thereby improving the surface finish and flatness of the rolled material. A larger roll diameter will increase the length of the deformation zone, thereby increasing the width expansion value. Considering the difficulty of biting the rolled piece and the deformation efficiency, the working roll diameter is preferably 350-600mm during pre-deformation. A faster rolling rate has a greater deformation resistance, and a too slow rolling rate and too fast temperature drop will also cause a greater deformation resistance and increase the difficulty of rolling. Therefore, it is more appropriate to control the angular velocity of the working roll to 0.8-6rad / s during rolling. Preferably, in order to improve the surface rolling effect, it is more appropriate to control the angular velocity of the working roll in the last pass to 6rad / s. The heating time of titanium billet is short, and only the surface layer can undergo plastic deformation after being heated. The single pass reduction is 5 to 20 mm, and 2 to 6 pre-deformation passes are performed. If the reduction is too small, the deformation layer cannot be produced. If the reduction is too large, the deformation resistance is large and rolling is difficult. The common grain size of EB billet is centimeter-level, and the grain size in the two-dimensional direction is mostly 20 to 50 mm. Therefore, the single pass is controlled to be 5 to 10 mm, and 2 to 6 pre-deformation passes are performed, with a cumulative reduction of 60 mm.
[0018] Through low-cost pre-deformation, a certain amount of stored energy is accumulated after the surface layer is rolled, so that the surface structure will recrystallize during subsequent heating, and the surface fine grain area will be used to improve the antioxidant capacity, reduce the diffusion depth of the hard α layer, and improve the coordinated deformation ability of the surface oxide layer and the matrix during the rolling of the finished product, thereby improving the surface quality.
[0019] S4 Slab Heating
[0020] The pre-deformed slab is sent to the heating furnace for heating and rolling. The slab has a certain temperature. After passing through the first and second heating zones of the heating furnace, it is kept in the 870℃~910℃ equalizing zone for 90~120min. The total time in the furnace is less than 300min, and the time in the heating zone is less than 180min. After the insulation, it is rolled out of the furnace. One of the heating zones is from room temperature to 550℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is less than 60min. The secondary heating zone is from 550℃ to 700~800℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is 100~120min. Segmented heating can avoid the uneven organization caused by overheating of the surface tissue, control the total re-furnace time, and avoid the serious surface oxygen absorption due to long-term heating.
[0021] The temperature range of the secondary heating zone of the slab is equal to the pre-treatment temperature of the pre-deformed slab, and the pre-deformed slab can be heated during the normal production of titanium coils, thereby improving production efficiency.
[0022] S5 black coil rolling: including rough rolling, finish rolling and slow cooling processes.
[0023] The slab is rolled into hot-rolled coils with a thickness of 3 to 12 mm and a width of 1700 to 2200 mm by a 2050 mm continuous rolling mill.
[0024] Rough rolling: The slab is rolled to a thickness of 40 to 60 mm through a rough rolling mill.
[0025] Finishing rolling: The slab is rolled to a thickness of 40-60mm by the rough rolling mill and then rolled by the finishing rolling unit to a thickness of 3-10mm. The finishing rolling inlet temperature is less than 820℃ and the final rolling temperature is greater than 720℃. The threading speed is 1.5-2.5m / s. TA1 and TA2 have good high-temperature plasticity. Slow threading can avoid tail swinging and ensure the straightness of the coil. The finishing rolling inlet temperature is controlled to be less than 820℃ because the finishing rolling zone is rolled at a high speed to avoid adiabatic heating caused by strain rate sensitivity to induce β phase transformation. After the phase transformation occurs, the Widmanstatten structure is easily formed in the subsequent cooling process. The Widmanstatten structure will deteriorate the mechanical properties of the titanium alloy coil. The final rolling must pass through the laminar cooling line, which is long and has a slow temperature drop. The final rolling temperature of less than 720℃ is not conducive to curling.
[0026] Slow cooling: After finishing rolling, the steel is coiled at a temperature of 550℃~600℃. After coiling, the steel is moved to the slow cooling zone for stack cooling at a temperature of 550℃ for 12~16h. After the insulation, the steel is taken out of the furnace for air cooling. Slow cooling in the slow cooling pit is beneficial to reducing residual stress and is beneficial to subsequent uncoiling.
[0027] S6 black leather coil continuous annealing
[0028] After hot rolling, the coil is cooled and then continuously annealed at 760℃~840℃. The thermal conductivity of titanium is λ=15.24W / (m·K), which is about 1 / 4 of nickel, 1 / 5 of iron, and 1 / 14 of aluminum. The thermal conductivity of various titanium alloys is about 50% lower than that of titanium. Therefore, it is necessary to strictly control the heating rate to ensure uniform heat transfer and sufficient insulation time. The uniform temperature zone length of the continuous annealing line is 50m, the travel speed is 2~5m / min, and the insulation time is ≥10min.
[0029] Furthermore, the performance of the TA1 and TA2 titanium alloy strips prepared by the above method was tested: After annealing, the TA1 and TA2 strips were prepared and tested according to GB / T 228.1-2021. The room temperature mechanical properties of TA1: R m ≥240MPa, 140MPa≤R p0.2 ≤310MPa, A≥30%; TA2: R m ≥400MPa, 275MPa≤R p0.2≤450MPa, A≥25%, in line with the mechanical properties requirements of GB / T 3621-2022 titanium and titanium alloy plates.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention aims at the bottleneck problem of many surface defects and poor structural uniformity after rolling of TA1 and TA2 smelted in the existing EB furnace. The preparation process of TA1 and TA2 titanium coils is comprehensively controlled from the aspects of titanium billet preparation, heating, rolling and heat treatment, thereby greatly improving the product quality of titanium coils.
[0032] The dense oxide film is formed on the surface of the slab at a temperature below 800℃, and the surface is rolled by gradient heating to prepare the surface deformation layer. Through low-cost pre-deformation, a certain amount of deformation storage energy is accumulated after surface rolling, so that the surface recrystallization structure is formed by subsequent heating, and the surface fine grain area is used to improve the oxidation resistance and reduce the depth of the hard α layer; compared with conventional titanium billets, the thickness of the oxygen permeation layer is controlled to be less than 80μm after heating in the heating furnace, and the coordinated deformation ability of the surface hard surface oxide layer and the matrix during rolling is improved, thereby improving the surface quality. In order to realize this method, a series of key parameters such as titanium billet pre-deformation mode, heating system, rolling deformation amount, etc. are proposed, and finally a wide hot-rolled titanium coil with a width of 1700-2200mm, a thickness of 3-10mm and good surface quality is prepared, which greatly improves the product quality, reduces the cost, and increases the yield rate, with good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The metallographic structure diagram of TA1 slab sample 1 obtained in Example 1;
[0034] Figure 2 The oxygen permeation layer depth diagram of TA1 slab sample 2 obtained in Example 1;
[0035] Figure 3 This is the metallographic structure diagram of the TA1 tape finished product sample 3 obtained in Example 1. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0037] A method for preparing TA1 and TA2 tapes, comprising the following steps:
[0038] S1 ingot smelting: Sponge titanium and vanadium aluminum alloy are used as raw materials, and smelted into TA1 and TA2 titanium alloy ingots with a thickness of (240-330 mm) × (1500-2000 mm) width × L mm through a vacuum electron beam cooling furnace;
[0039] S2 Slab grinding: Slab grinding, six-sided milling thickness 10-20mm; length direction, four long sides chamfered 40-60mm; width direction, four wide sides chamfered 50-80mm;
[0040] S3 slab pre-deformation: The slab to be rolled is surface-grinded to expose the bright metal, and the surface roughness Ra is less than 3.2μm; after grinding, the slab is loaded into the furnace, and the slab is rotated 90° after loading; the slab is quickly moved to the 700℃~800℃ temperature zone by the walking beam and kept warm for 30~60min, and after being taken out of the furnace, it is rotated 90° and fed for pre-deformation rolling;
[0041] S4 slab heating: the pre-deformed slab is sent to the heating furnace for heating and rolling. After passing through the first and second heating zones of the heating furnace, the slab is kept in the 870℃~910℃ soaking zone for 90~120min; the total time in the furnace is less than 300min, the time in the heating zone is less than 180min, and the slab is taken out of the furnace for rolling after the end of the insulation;
[0042] S5 black coil rolling: including rough rolling, finishing rolling and slow cooling process, the slab is rolled into hot rolled coil with thickness of 3-12mm and width of 1700-2200mm by 2050mm continuous rolling mill;
[0043] S6 black coil continuous annealing: After hot rolling, the coil is cooled and then continuously annealed, the annealing temperature is 760℃~840℃; the continuous annealing line has an average temperature zone length of 50m, a travel speed of 2~5m / min, and a holding time of ≥10min.
[0044] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.
[0045] Example 1
[0046] A TA1 tape preparation method, the specific process flow is:
[0047] S1 Ingot Melting
[0048] A method for preparing a titanium alloy coil is disclosed. Sponge titanium, vanadium aluminum alloy, etc. are used as raw materials, and TA1 ingots are smelted by a vacuum electron beam cooling hearth furnace (EB furnace). The ingot element range conforms to the titanium and titanium alloy grade and chemical composition standard GB / T 3620.1-2016, and the ingots are smelted into 240 mm thick × 1500 mm wide × 6500 mm slabs.
[0049] S2 Slab Preparation
[0050] Slab grinding: six-sided milling thickness 10mm;
[0051] In the length direction, the four long sides are chamfered 40mm;
[0052] In the width direction, the four wide sides are chamfered 50mm.
[0053] S3 slab pre-deformation
[0054] (1) The surface of the slab to be rolled is polished until the fresh metallic color is exposed, and the surface roughness is Ra = 3.0 μm. After polishing, the slab is loaded into the furnace and quickly moved to the 700°C temperature zone by the walking beam for 60 minutes of heat preservation before being taken out of the furnace for pre-deformation.
[0055] (2) After the slab is loaded into the furnace, it is rotated 90° and the titanium slab is erected.
[0056] (3) After the insulation is completed, the material is rotated 90° and fed for rolling.
[0057] (4) After the material is centered, it is pre-deformed by a four-roll mill. The length of the working roll is 2000 mm, the diameter of the working roll is 350 mm, and 6 pre-deformations are performed. The angular velocity of the working roll in the first 5 passes is 0.8 rad / s, and the deformation of each pass is 5 mm. The angular velocity of the working roll in the 6th pass is 6 rad / s, and the deformation of each pass is 5 mm, and the cumulative deformation is 30 mm.
[0058] Through low-cost pre-deformation, a certain deformation layer strain is accumulated after the surface layer is rolled, so that a fine-grained structure of the surface layer can be formed by subsequent heating.
[0059] S4 Slab Heating
[0060] The pre-deformed slab is sent to the heating furnace for heating and rolling. The slab has a certain temperature. After passing through the first and second heating zones of the heating furnace, it is sent to the 910℃ equalizing zone for 90 minutes of insulation. The total time in the furnace is 270 minutes, and the heating zone is 180 minutes. After the insulation is completed, it is taken out of the furnace for rolling. One of the heating zones is from room temperature to 550℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is 60 minutes. The second heating zone is from 550℃ to 800℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is 120 minutes. The slab tail is cut and sampled for testing. The surface metallographic structure can be seen. Figure 1 , the depth of oxygen permeable layer is Figure 2 , the oxygen penetration depth is about 50μm.
[0061] S5 black leather roll rolling
[0062] The slab is rolled into a hot-rolled coil with a thickness of 3mm and a width of 1700mm by a 2050mm continuous rolling mill. The slab is rolled to a thickness of 40mm by a rough rolling mill and then rolled to 3mm by a finishing mill. The finishing inlet temperature is 800℃, and the threading speed is 1.5m / s. TA1 has good high-temperature plasticity. Slow threading can avoid tail swinging and ensure the straightness of the coil. The finishing inlet temperature is controlled to be less than 820℃, and the final rolling temperature is 730℃.
[0063] After finishing rolling, the steel is coiled at a temperature of 600°C. After coiling, it is moved to the slow cooling zone for stack cooling at a temperature of 600°C for 12 hours. After the end of the insulation, it is taken out of the furnace for air cooling. Slow cooling in the slow cooling pit is beneficial to reducing residual stress and is conducive to subsequent uncoiling.
[0064] S6 black leather coil continuous annealing
[0065] After hot rolling, the coil is cooled and then continuously annealed. The annealing temperature is 840°C, the uniform temperature zone length of the continuous annealing line is 50m, the travel speed is 2m / min, and the holding time is 25min.
[0066] S7 performance test
[0067] After annealing, the TA1 coil was subjected to tensile test according to GB / T228.1-2021. The room temperature mechanical properties R p0.2 210MPa, R m It is 320MPa, A=42%, which meets the mechanical property requirements of titanium and titanium alloy plates in GB / T3621-2023. The average grain size is 5.5. The metallographic photo of the finished sample 3 is as follows: Figure 3 As shown, they are uniform in size.
[0068] Example 2
[0069] A TA2 tape preparation method, the specific process flow is:
[0070] S1 Ingot Melting
[0071] A method for preparing a titanium alloy coil is disclosed. Sponge titanium, vanadium aluminum alloy, etc. are used as raw materials, and TA2 ingots are smelted by a vacuum electron beam cooling hearth furnace (EB furnace). The ingot element range conforms to the titanium and titanium alloy grade and chemical composition standard GB / T 3620.1-2016, and the ingots are smelted into 330 mm thick × 2000 mm wide × 7200 mm slabs.
[0072] S2 Slab Grinding
[0073] Slab grinding: six-sided milling thickness 20mm;
[0074] In the length direction, the four long sides are chamfered 40mm;
[0075] In the width direction, the four wide sides are chamfered 50mm.
[0076] S3 slab pre-deformation
[0077] (1) The surface of the slab to be rolled is polished until the fresh metallic color is exposed, and the surface roughness is Ra = 2.8 μm. After polishing, the slab is loaded into the furnace and quickly moved to the 800°C temperature zone by the walking beam for 60 minutes of heat preservation before being taken out of the furnace for pre-deformation.
[0078] (2) After the slab is loaded into the furnace, it is rotated 90° and the titanium slab is erected.
[0079] (3) After the insulation is completed, the material is rotated 90° and fed for rolling.
[0080] (4) After the material is centered, it is pre-deformed by a four-roll mill. The length of the working roll is 2000 mm, the diameter of the working roll is 600 mm, and 4 pre-deformations are performed. The angular velocity of the working roll in the first 3 passes is 0.8 rad / s, and the deformation of each pass is 10 mm. The angular velocity of the working roll in the 4th pass is 6 rad / s, and the deformation of each pass is 10 mm, and the cumulative deformation is 40 mm.
[0081] Through low-cost pre-deformation, a certain deformation layer strain is accumulated after the surface layer is rolled, so that a fine-grained structure of the surface layer can be formed by subsequent heating.
[0082] S4 Slab Heating
[0083] The pre-deformed slab is sent to the heating furnace for heating and rolling. The slab has a certain temperature. After passing through the first and second heating zones of the heating furnace, it is kept in the 870℃ equalizing zone for 120 minutes. The total time in the furnace is 300 minutes, and the heating zone is 120 minutes. After the end of the insulation, it is rolled out of the furnace. One of the heating zones is from room temperature to 550℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is 60 minutes. The secondary heating zone is from 550℃ to 700℃, and the slab is sent by the walking beam to control the heating temperature zone. The heating time is 120 minutes.
[0084] S5 black leather roll rolling
[0085] The slab is rolled into a hot-rolled coil with a thickness of 12mm and a width of 2200mm by a 2050mm continuous rolling mill. The slab is rolled to a thickness of 60mm by a rough rolling mill and then rolled to 12mm by a finishing mill. The finishing inlet temperature is 780℃, the threading speed is 2.5m / s, TA2 has good high-temperature plasticity, slow threading can avoid tail swinging, ensure the straightness of the coil, control the finishing inlet temperature to be less than 800℃, and the final rolling temperature is 700℃.
[0086] After finishing rolling, the steel is coiled at a temperature of 550°C. After coiling, it is moved to the slow cooling zone for stack cooling at a temperature of 550°C for 12 hours. After the end of the insulation, it is taken out of the furnace for air cooling. Slow cooling in the slow cooling pit is beneficial to reducing residual stress and is conducive to subsequent uncoiling.
[0087] S6 black leather coil continuous annealing
[0088] After hot rolling, the coil is cooled and then continuously annealed. The annealing temperature is 760°C, the uniform temperature zone length of the continuous annealing line is 50m, the travel speed is 2m / min, and the holding time is 25min.
[0089] S7 performance test
[0090] After annealing, the TA2 coil was subjected to tensile test according to GB / T228.1-2021. The room temperature mechanical properties R p0.2 360MPa, R m It is 460MPa, A=35%, which meets the mechanical property requirements of titanium and titanium alloy plates in GB / T 3621-2022.
[0091] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing TA1 and TA2 tapes, characterized in that: The preparation method comprises the following steps: S1 ingot smelting: Sponge titanium and vanadium aluminum alloy are used as raw materials, and smelted into TA1 and TA2 titanium alloy ingots with a thickness of (240-330 mm) × (1500-2000 mm) width × L mm through a vacuum electron beam cooling furnace; S2 Slab grinding: Slab grinding, six-sided milling thickness 10-20mm; length direction, four long sides chamfered 40-60mm; width direction, four wide sides chamfered 50-80mm; S3 slab pre-deformation: The slab to be rolled is surface-grinded to expose the bright metal, and the surface roughness Ra is less than 3.2μm; after grinding, the slab is loaded into the furnace, and the slab is rotated 90° after loading; it is moved to the 700℃~800℃ temperature zone by the walking beam and kept warm for 30~60min, and after being taken out of the furnace, it is rotated 90° and fed for pre-deformation rolling; S4 slab heating: the pre-deformed slab is sent to the heating furnace for heating and rolling. After passing through the first and second heating zones of the heating furnace, the slab is kept in the 870℃~910℃ soaking zone for 90~120min; the total time in the furnace is less than 300min, the time in the heating zone is less than 180min, and the slab is taken out of the furnace for rolling after the end of the insulation; S5 black coil rolling: including rough rolling, finishing rolling and slow cooling process, the slab is rolled into hot rolled coil with thickness of 3-12mm and width of 1700-2200mm by 2050mm continuous rolling mill; S6 black coil continuous annealing: After hot rolling, the coil is cooled and then continuously annealed, the annealing temperature is 760℃~840℃; the continuous annealing line has an average temperature zone length of 50m, a travel speed of 2~5m / min, and a holding time of ≥10min.
2. The preparation method according to claim 1, characterized in that: The pre-deformation rolling described in step S3 includes: pre-deformation rolling through a four-roll rolling mill after feeding and centering, the working roll body length is greater than 2000mm, the working roll diameter is 350-600mm, the working roll angular velocity during rolling is 0.8-6rad / s, the single-pass deformation amount is 5-10mm, 4-6 pre-deformation passes are performed, and the cumulative reduction amount is 60mm.
3. The preparation method according to claim 1, characterized in that: In step S4, the first heating zone is heated from room temperature to 550°C, and the blank is delivered by a walking beam, and the heating time of the heating zone is controlled to be less than 60 minutes; the secondary heating zone is heated from 550°C to 700-800°C, and the blank is delivered by a walking beam, and the heating time of the heating zone is controlled to be 100-120 minutes.
4. The preparation method according to claim 1, characterized in that: Rough rolling in step S5: The slab is rolled to a thickness of 40 to 60 mm by a rough rolling mill.
5. The preparation method according to claim 1, characterized in that: In step S5, the finishing rolling entrance temperature is less than 820°C, the final rolling temperature is greater than 720°C, and the strip threading speed is 1.5-2.5 m / s; after finishing rolling, the strip is curled at a temperature of 550°C-600°C, and after curling, the strip is moved into a slow cooling zone for stack cooling at a temperature of 550°C for 12-16 hours.
Citation Information
Patent Citations
Multifunctional titanium alloy and preparation method and application thereof
CN112063887A
Preparation method of titanium alloy hot-rolled coil
CN113215509A
Process method for rolling pure titanium coiled plates in small batch
CN114130815A
Rolling method for smelting titanium blank in EB furnace
CN117463784A
Preparation method of high-elongation narrow pure titanium foil
CN118595205A
Cited By
Temperature control method and system for cold continuous rolling unit and cold continuous rolling unit
CN121467483A
